Acute Respiratory Distress Syndrome (ARDS) (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Acute respiratory distress syndrome (ARDS), which is marked by severe inflammation and poor gas exchange, poses a significant challenge. ARDS research has advanced in the past ten years as we have enhanced our understanding of the range of presentations, the significance of focusing on particular pathophysiological processes, and how these can affect each patient's response to treatment in the context of personalized medicine. Despite advancements in supportive care, mortality rates remain high, underscoring the urgent need for customized treatment regimens. With an emphasis on the need to tailor treatments to each patient's particular profile, this Special Issue aimed to explore innovative approaches to the treatment of ARDS. The contributions to this Specail Issue cover a wide range of topics, such as the utilization of advanced imaging techniques to monitor lung function, the use of biomarkers to predict treatment response, and the application of machine learning algorithms in therapeutic decision-making. Additionally, novel medications and adjunctive or rescue treatments such as extracorporeal membrane oxygenation (ECMO) and immunomodulatory therapies are discussed. By promoting interdisciplinary collaboration and the dissemination of innovative research, this Special Issue investigated the path to more effective, customized therapy for ARDS patients. This Special Issue presents articles that address the pathophysiology and classification of ARDS, pharmacological and supportive therapies, chest imaging, and the identification of biological sub-phenotypes as a target for possible novel treatment strategies.